Unambiguous observation of F-atom core-hole localization in CF4 through body-frame photoelectron angular distributions - McCurdy, C. W.; Rescigno, T. N.; Trevisan, C. S.; Lucchese, R. R.; Gaire, B.; Menssen, A.; Schöffler, M. S.; Gatton, A.; Neff, J.; Stammer, P. M.; Rist, J.; Eckart, S.; et al. (My University, 2017)
A dramatic symmetry breaking in K-shell photoionization of the CF4 molecule in which a core-hole vacancy is created in one of four equivalent fluorine atoms is displayed in the molecular frame angular distribution of the photoelectrons. Observing the photoejected electron in coincidence with an F+ atomic ion after Auger decay is shown to select the dissociation path where the core hole was localized almost exclusively on that atom. A combination of measurements and ab initio calculations of the photoelectron angular distribution in the frame of the recoiling CF3+ and F+ atoms elucidates the underlying physics that derives from the Ne-like valence structure of the F(1s-1) core-excited atom. © 2017 American Physical Society.
Citation: McCurdy, C. W., Rescigno, T. N., Trevisan, C. S., Lucchese, R. R., Gaire, B., Menssen, A., . . . Weber, T. (2017). Unambiguous observation of F-atom core-hole localization in CF4 through body-frame photoelectron angular distributions. Physical Review A, 95(1). doi:10.1103/PhysRevA.95.011401
Keywords: Atoms; Calculations; Fluorine; Photoelectrons; Photons; Ab Initio Calculations